ANALISIS PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DI COFFE SOUL LUBUKLINGGAU - Rifa Khairunnisa Bakri; Arisky Andrinaldo; Adhelian Sabtri Dj; Dea Hervy Ramadhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of the implementation of the Accounting Information System (SIA) on the quality of financial statements at Coffee Soul Lubuklinggau. The importance of SIA in supporting the accuracy, relevance, and timeliness of financial report preparation is the basis of this study. The research method used was quantitative, with data collection through questionnaires, interviews, and documentation. The data analysis technique was performed by simple linear regression (or multivariate, if there is a control variable). The results of the study show that the implementation of the Accounting Information System has a positive and significant influence on the quality of financial statements at Coffee Soul Lubuklinggau, that is, the better the implementation of SIA, the higher the quality of the financial statements produced. These findings are consistent with previous studies such as those conducted by the Effect of the Application of Accounting Information Systems on the Quality of Financial Statements at PT. CSM Cargo, which also found a significant influence of SIA on the quality of financial statements. In addition, the literature on studies such as the Influence of Accounting Information Systems, Information Technology, and Human Resource Quality on the Quality of Financial Statements also supports that SIA is an important determinant for the quality of financial statements. The conclusion of this study confirms that increasing the implementation of SIA at Coffee Soul Lubuklinggau can be a key factor in improving the reliability, relevance, and timeliness of financial statements. Therefore, it is recommended that Coffee Soul management continue to improve and optimize the accounting information system, as well as ensure the understanding and competence of the staff who use the system so that the results of financial statements are of higher quality and reliability.